An Introduction to property theory - Alexander, Gregory S. (Cambridge introductions to philosophy and law, 2012)
"This book surveys the leading modern theories of property - Lockean, libertarian, utilitarian/law-and-economics, personhood, Kantian and human flourishing - and then applies those theories to concrete contexts in which property issues have been especially controversial. These include redistribution, the right to exclude, regulatory takings, eminent domain and intellectual property. The book highlights the Aristotelian human flourishing theory of property, providing the most comprehensive and accessible introduction to that theory to date. The book's goal is neither to cover every conceivable theory nor to discuss every possible facet of the theories covered. Instead, it aims to make the major property theories comprehensible to beginners, without sacrificing accuracy or sophistication. The book will be of particular interest to students seeking an accessible introduction to contemporary theories of property, but even specialists will benefit from the book's lucid descriptions of contemporary debates"--